50th International Eucharistic Congress. Proceedings of the International Symposium of Theology. The Ecclesiology of Communion Fifty Years after the Opening of Vatican II - Nadbrzeżny, Antoni (Studia Nauk Teologicznych PAN, 2020)
Recenzja